A framework for knowledge retention to support business continuity in the cross-border mergers of the telecommunications industry in Lesotho - Tseole, Tahleho; Marutha, Ngoako Solomon (VINE journal of information and knowledge management systems, 2024)
Purpose The purpose of this study is to investigate a framework for knowledge retention to support business continuity in cross-border mergers of the telecommunications industry in Lesotho. Design/methodology/approach This study applied a qualitative case study, with data collected through interviews from a purposively selected sample of staff members who held managerial positions. Information in this study was partially extracted from the PhD thesis of Dr Tseole ET supervised by Prof Ngulube P at the University of South Africa completed in 2021. Findings The study discovered that a considerable amount of knowledge may have been lost because employees who either left the organisation or those who were apparently forced to resign during the process had left without any proper knowledge retention arrangements. Research limitations/implications The framework proposed in this study may be used in framing future studies as a theoretical framework. The study also provides new literature for review and discussion of background in future related studies. Practical implications The framework provided in the study may be used as a benchmark in the knowledge management industry and/or organisations for policy development or improvements and implementation of knowledge retention strategies. Social implications Through recommendations and framework provided by this study, organisations will be able to improve their services to their sphere of influence in the surrounding communities. So, community will be receiving an improved and good service at all the times. Originality/value A framework for facilitating knowledge retention in the cross-border mergers of the telecommunications industry is therefore proposed and the researchers believe it will be helpful to the organisation for improving knowledge retention going forward, particularly in the merger process.